Jogos diferenciais estocásticos: controle e parada ótimos - Messias, Alan Teixeira Nicácio de (2018)
In this work, we analyze a zero-sum non-Markovian stochastic diferential game via martingale methods. The stochastic game consists of two players, namely the controller and stopper which keep track the game via stochastic controls summarized by strategies and stopping times respectively. Our main goal is to prove the game has a value and it admits a saddle point. Our work is based on Karatzas & Ingrid-Mona Zamfirescu’s paper [1].